Potret Komunitas Muslim di Korea Selatan: Studi kasus Korea Muslim Federation (KMF), 1990-2020 - Nabila Paradays (Socio Historica: Journal of Islamic Social History, 2022)
This article discusses the development of Islam and the diverse Muslim community in South Korea from 1990-2020. The Korea Muslim Federation (KMF), bridging the relationship between the Muslim minority in Korea and the global Muslim community, builds networks and seeks to spread Islam widely in South Korea. Having a network allows for relationships that provide convenience and unlimited connections, bridging diverse individuals or communities. Islam in South Korea exists as a minority community, through the connections and networks built by the Korean Muslim Federation with the global Muslim community, both Islam and the Muslim community have received a lot of support and kindness from various global Muslim organizations. Relationships are established on the basis of brotherhood and care among fellow Muslims. KMF's network with global Muslims is a type of social capital that bridges communities, groups, or organizations.The social capital theory is used to understand the phenomena that occur and answer the questions in this study. Through the social relations established by the Korean Muslim Federation (KMF) with the global Muslim community, Islam developed widely in South Korea as a minority community, and the Muslim community grew as a multicultural Muslim society from 1990 to 2020.Artikel ini membahas perkembangan Islam dan Komunitas Muslim di Korea Selatan yang beragam pada tahun 1990-2020. Korea Muslim Federation (KMF), menjembatani hubungan antara minoritas Muslim di Korea dengan komunitas Muslim global, membangun jaringan dan berupaya menyebarkan Islam secara luas di Korea Selatan. Memiliki jaringan memungkinkan terjadinya hubungan yang memberikan kemudahan dan koneksi tak terbatas, menjembatani antara individu yang beragam ataupun antar komunitas. Islam di Korea Selatan hadir sebagai komunitas minoritas, lewat koneksi dan jaringan yang di bangun oleh Korea Muslim Federation dengan komunitas Muslim global, baik Islam maupun komunitas Muslim telah menerima banyak dukungan dan kebaikan dari berbagai organisasi Muslim global. Hubungan terjalin atas dasar persaudaraan dan kepedulian antar sesama Muslim. Jaringan KMF dengan Muslim global merupakan jenis modal sosial yang menjembatani antara komunitas, kelompok atau organisasi.Teori modal sosial digunakan untuk memahami fenomena yang terjadi dan menjawab pertanyaan dalam penelitian ini. Lewat hubungan sosial yang dijalin oleh Korea Muslim Federation (KMF) dengan komunitas Muslim Global, Islam berkembang secara luas di Korea Selatan sebagai komunitas Minoritas, dan komunitas Muslim tumbuh sebagai masyarakat Muslim multikultural pada tahun 1990 sampai 2020.